Association between non-healing precancerous oral lesions and ulcers with tobacco smoking: A population-based study - Olawale Olatunbosun Adamson; Olufemi Erinoso; Remilekun Oluwakuyide; Abiodun Amao; Olajumoke Effiom; Olalekan Micah Gbotolorun (Oral Oncology Reports)
Background: This study aims to identify early detection of precancerous lesions amongst high-risk individuals (motor park workers). Though anecdotal evidence suggests they are high users of alcohol, marijuana, and cigarette smoking which are prominent risk factors for the occurrence of oral cancers the occurrence of precancerous lesions in this group has not been determined. Method: This was a prospective cross-sectional study of a target population of motor park workers (40 years and above). Participants were selected from motor parks in Lagos. All participants had an examination of oral mucosa done for pre-cancerous or cancerous lesions. All suspected mucosa were stained with toluidine blue. All positively stained mucosa were repeated after 1 week for confirmation blue for suspicious cases. Positive cases were biopsied and histology was determined. Result: A total of 453 participants completed the survey. The mean age of participants was 39.4 years (SD: 12.5), 52.8 % were male, while 47.2 % were female. A majority of ever and current smokers did not have oral ulcers, and all the participants with oral ulcers did not indicate a history of smoking. a history of ever-smoking was significantly associated with higher odds of oral lesions in both bivariate (OR: 4.58; 95 % CI: 2.04,10.29; p:<0.001) and multivariate models (OR:2.76). Conclusion: Smoking was significantly associated with oral pre-cancerous lesions in this study.